THE LITERATURE OF THE ARAB DIASPORA (MAHJAR) IN EUROPE: HISTORY, CHARACTERISTICS AND MAHJAR LITERATURE - Nadhita Chilwina; Firsya Aulia Putri (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The term diaspora (Mahjar) refers to Arab writers who move from their home countries to other countries by bringing Arabic literary works to be disseminated in the country's territory. Thus, diasporic Arabic literature (Mahjar) is a sign of the early stages of the development of Arabic literature in the modern century because it is the result of a mixture of two cultures, namely East and West. This research aims to trace Mahjar's history, characteristics, and literature in the European region. This research uses qualitative research with a library research method. The research data sources used in this research are secondary data sources only. The results of this study indicate that the emergence of Mahjar Arabic literature in Europe began with Napoleon's arrival in Egypt with political and pragmatic objectives in 1798, which at that time also had a vast influence on the Arab nation. The characteristics of diasporic Arabic literature (Mahjar) show that diasporic Arabic literature (Mahjar) is more decadent than classical literature and has literary themes more inclined to realism. The Mahjar literary figures in Europe include Khalil Mutran, Abbas Beydoun, Habib Abdulrab Sarori, and Osman Engin.